Pengaruh Work Life Balance dan Stres Kerja Terhadap Kinerja Karyawan Bagian Packing di Warehouse XYZ Kabupaten Bandung Barat - Gheamaura Regitavagayo; R.M Juddy Prabowo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Human resource management is a company's most crucial component. The company will benefit from optimal employee performance, which can be attained by focusing on work life balance and the stress that employees face at work.. Based on data on decreased performance and increased absenteeism in packing section employees at Warehouse XYZ, West Bandung Regency, the problem is caused by a lack of attention to work life balance and work stress. This investigation aims to identificate the way work life balance and work stress affect the performance of packing section employees at Warehouse XYZ West Bandung Regency. This study employs a quantitative methodology, gathering data via questionnaires. The 32 participants who were employed in Warehouse XYZ's packing department made up the research sample. Multiple linear regression analysis, instrument testing, the classical assumption test, and hypothesis testing were used to analyze the data utilizing SPSS version 27. The findings demonstrated that while work stress has a detrimental impact on employee performance, work-life balance has a positive impact. Employee performance is impacted by both work-life balance and work stress. The packing section staff at Warehouse XYZ West Bandung Regency will perform exceptionally well if they have a very balanced work life balance and little to no job stress.